2016
DOI: 10.1364/boe.7.000648
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal 3D cancer-mimicking optical phantom

Abstract: Three-dimensional (3D) organ-mimicking phantoms provide realistic imaging environments for testing various aspects of optical systems, including for evaluating new probe designs, characterizing the diagnostic potential of new technologies, and assessing novel image processing algorithms prior to validation in real tissue. We introduce and characterize the use of a new material, Dragon Skin (Smooth-On Inc.), and fabrication technique, air-brushing, for fabrication of a 3D phantom that mimics the appearance of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Silicone (Dragon Skin ® 30, Smooth‐On, Macungie, PA, USA, ρ = 1.08 g/cm³) was used for the soft tissue (mediastinum, muscles, fat, skin) and was cast into the mold of the body contour that was 3D printed using SLS. Dragon Skin is a silicone‐based polymer that has been used in phantoms before . This material was chosen because its density is close to water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Silicone (Dragon Skin ® 30, Smooth‐On, Macungie, PA, USA, ρ = 1.08 g/cm³) was used for the soft tissue (mediastinum, muscles, fat, skin) and was cast into the mold of the body contour that was 3D printed using SLS. Dragon Skin is a silicone‐based polymer that has been used in phantoms before . This material was chosen because its density is close to water.…”
Section: Methodsmentioning
confidence: 99%
“…Dragon Skin is a silicone-based polymer that has been used in phantoms before. 23,24 This material was chosen because its density is close to water. Furthermore, Dragon Skin is easily molded due to its high elasticity, which allowed clean removal of the phantom from the 3D-printed mold.…”
Section: B Manufacturing Of the 3d Model And 3d Printingmentioning
confidence: 99%
“…32 3-D printing is also becoming a popular method for fabricating phantom molds and for manufacturing the phantoms themselves. [33][34][35] The phantom fabrication methods used here are described in full detail by Durkee et. al.…”
Section: Measured Optical Properties Of Mouse Lungmentioning
confidence: 99%
“…[10] Three-dimensional organ-mimicking phantoms provide realistic imaging environments for testing various aspects of optical systems and assessing novel image processing algorithms. [11] Murphy summarized the technological innovations in the field of ureterorenoscopy and concluded that the ongoing developments in virtual 3D imaging, and wireless endoscopy continue to create opportunities to improve the endoscopic urologic procedures. [12] An interesting study, although with limited number of patients, demonstrated that 3D reconstruction cloacagrams yielded similar results to endoscopic findings.…”
Section: Clinical and Research Consequencesmentioning
confidence: 99%